TCP CUBIC with HyStart: Congestion Control for Satellite Communication in OMNeT++ INET - Martino, Luigi; Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (2024 IEEE 29th Asia Pacific Conference on Communications (APCC), 2024)
In the context of satellite communication, unique challenges arise, such as long delay links that can impact the network performance also at the Transport Layer. With regard to the Transmission Control Protocol (TCP), congestion control plays a crucial role in managing network traffic and ensuring efficient data transmission over the Internet. This paper wants to give an overview of how TCP congestion control mechanisms adapt to mitigate the effects of long link delays, highlighting the importance of optimizing protocols for these specific environments. Within this context, where signals travel extended distances, traditional TCP algorithms designed for terrestrial networks with relatively low latency, may struggle to maintain optimal performance. As a result, specialized congestion control algorithms, like TCP CUBIC, can be employed to address these challenges. Through the integration of TCP CUBIC with HyStart within a simulation framework based on OMNeT++ and INET, this study sheds light on the importance of tailoring congestion control strategies to suit specific network environments including satellite communicatio